Flow visualisation for bench top wind tunnel - Tan, Clinton Jing Xue (Nanyang Technological University, 2023)
This report describes a project that is aimed at enhancing the flow visualisation capabilities of the bench-top wind tunnel by modifying the smoke delivery system and the method of capturing the smoke visualisation. The experiments conducted have proven successful in achieving the objective, and high-quality images of the smoke visualisation have been obtained. Over the course of this project, two design iterations had been carried out, with the fifth iteration addressing the previous shortcomings and the sixth iteration which employs a modification to the smoke rake design with a symmetrical aerofoil profile to enhance the smoke flow quality. These improvements have resulted in a much more streamlined flow across the test objects, thereby significantly improving the flow visualisation quality. The results obtained confirm the effectiveness of the enhancements made to the existing wind tunnel, which is comparable to other wind tunnel projects in the industry.